Constitutional Rights of Citizen Journalism in Indonesia: From Maqashid Sharia Perspective - Fuqoha, Fuqoha; Mulyasih, Rahmi; Hasuri, Hasuri; Firdausi, Indrianti Azhar; Barten, Silfi (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
The conception of a democratic rule of law in Indonesia has implications for the social and law order as a protection for the citizens. The protections guarantee the rights and responsibilities of every person regulated or protected by a democratic state. Either of the rights protected by the constitutions of Indonesia is guaranteed in obtaining and conveying information. As a profession, it is a part of journalistic activities, both professional and citizen journalism, as a constitutionally inherent right. The problem encountered is protection for citizen journalism, which is not regulated as protection for journalists in the legal system of the press. This research employed a qualitative model with a normative juridical approach to conceptualise the laws with facts and phenomena of journalistic activities. The analysis aims to assert that every person has a constitutional right to obtain and convey information like a professional journalist. A law is responsible for citizen journalism based on the law system of the press and code of ethics, which places citizen journalism products as a part of the news on press channels or press companies as the objects of the media that publish information. The concept of the principles of citizen journalism is related by maqashid shariah in Islam, which includes al-ahkam al-khamsah, namely religious protection (hifz al-din), protection of the soul (hifz al-nafs), protection of offspring (hifz al-nasl), protection of ideas/thoughts (hifz al-'aql), and protection of property (hifz al-mal).